FunGeCo: a web-based tool for estimation of functional potential of bacterial genomes and microbiomes using gene context information - Anand, Swadha; Kuntal, Bhusan K.; Mohapatra, Anwesha; Bhatt, Vineet; Mande, Sharmila S. (2020)
Motivation: Functional potential of genomes and metagenomes which are inferred using homology-based methods are often subjected to certain limitations, especially for proteins with homologs which function in multiple pathways. Augmenting the homology information with genomic location of the constituent genes can significantly improve the accuracy of estimated functions. This can help in distinguishing cognate homolog belonging to a candidate pathway from its other homologs functional in different pathways. Results: In this article, we present a web-based analysis platform `FunGeCo' to enable gene-context-based functional inference for microbial genomes and metagenomes. It is expected to be a valuable resource and complement the existing tools for understanding the functional potential of microbes which reside in an environment.